PEMBUNUHAN SEBAGAI PENGHALANG HAK WARIS DALAM PERSPEKTIF HUKUM ISLAM DAN QOWAID FIQHIYAH - Muhammad Idris; Sayehu; Usman (Fakultas Agama Islam UNISMA, 2023)
Inheritance law is the law that regulates the transfer of assets left behind by someone who has died, as well as the consequences for their heirs. That is, in inheritance it is regulated who has the right to inherit, as well as things that cause obstacles to heirs in obtaining inheritance. One of the reasons an heir does not receive an inheritance is murder committed by the heir to the heir. This is based one someone’s intention to speed up obtaining inheritance. This research uses a library study method by taking data sources from books and scientific works, then the author will analyze the data. The aim of this research is to determine the review of qowaid fiqhiyah and islamic law regarding murder which is an obstacle to inheritance rights. The results of this research show that cases of murder which cause someone to be prevented from obtaining an inheritance are still a mistake among madzahib arba’ah and the diffrence lies in intentional and unintentional murder. Murder commited by the heir against the heir can prevent him from getting the inheritance, this is in accordance with the rules of fiqh “whoever is in a hurry to get something before the time, he may be judged as haram for getting it”. Keywords: heir, inheritance, murder.